Efficacy and safety of eravacycline versus tigecycline for complicated intra-abdominal infections in the ICU: a multicenter, single-blind, parallel randomized controlled trial study protocol - Liu, Jin Jie; Guo, Dong Dong; Wang, Meng Xing; Li, Yan Zhao; Li, Hang; Liu, Si Bo; Yang, Rong Li; Zhang, Dian Hong (Frontiers in Medicine, 2024)
Background: Complicated intra-abdominal infections (cIAIs), often caused by multidrug-resistant bacteria such as carbapenem-resistant A. baumannii (CRAB) and carbapenem-resistant Enterobacteriaceae (CRE) are a critical challenge in ICUs. Owing to their high mortality and treatment failure rates, there is an urgent need for effective therapies. This trial will compare eravacycline to tigecycline for treating cIAIs in patients in the ICU, aiming to provide a superior treatment option.Methods: This is a multicenter, single-blind, parallel randomized controlled trial. Adult patients in the ICU with complex abdominal infections who meet the eligibility criteria will be included. The main outcome is the all-cause 30-day mortality of patients in clinically evaluable and microbiologically evaluable populations. Secondary outcomes include the proportion of total responsive patients in the clinically evaluable population at the end of treatment and test of cure visits; the proportion of total responsive patients in the microbiologically evaluable population at the end of treatment and test of cure visits; and ICU hospitalization time and costs. Safety assessments include the incidence of various adverse events and changes in clinical laboratory test results. The subjects will be randomly assigned to receive treatment with either eravacycline or tigecycline at a 1:1 ratio. The all-cause mortality rates of patients treated with eravacycline and TGC were 17.7% and 18.7%, respectively, with an estimated actual mortality rate of 0.95. A total sample size of 262 subjects is required to reach 80% power with an α of 0.05. Considering a 10% loss rate, 292 patients will be enrolled and randomly assigned to the three groups in equal proportions.This trial was approved by the Ethics Committee of Ansteel Group General Hospital. The communication plan includes presentations at scientific conferences, scientific publications, and presentations to the public through nonprofessional media.